Predictors of Response to Oral Medications and Low-Histamine Diet in Patients with Chronic Urticaria - Hui-Ling Chiang; Chen-Hung Chen; Malcolm Koo; Tzung-Yi Tsai; Cheng-Han Wu (Journal of Immunology Research)
Background. Chronic urticaria (CU) is comprised of diverse phenotypes, and thus, a shift towards a precision medical approach is warranted in its management. Methods. This study enrolled 78 patients with CU. Serum erythrocyte sedimentation rate, hemoglobin, hematocrit, eosinophil count, IgE, antinuclear antibody (ANA), and serum diamine oxidase (DAO) levels of the patients were measured and were compared according to the patient’s response to second-generation antihistamines (sgAH), corticosteroids, leukotriene receptor antagonist (LTRA), H2 blockers, and low-histamine diet. Results. Age- and sex-adjusted logistic regression analysis showed that patients with duration of CU>3 years (adjusted odd ratio aOR=4.39) and a DAO level<10 U/mL (aOR=3.90) were significantly associated with a good sgAH response. Age>50 years (aOR=0.02), duration of chronic urticaria>3 years (aOR =0.06), and an ANA titer≥1:80 (aOR=0.03) were significantly and inversely associated with corticosteroid response. A low-histamine diet response was significantly associated with LTRA response (aOR=67.29). In addition, a DAO level<5.4 U/mL (aOR=71.95) was significantly associated with H2 blocker response. Furthermore, concomitant angioedema (aOR=10.56), multiple food triggers (aOR=11.69), and a DAO level<5.4 U/mL (aOR=3.78) were significantly associated with a low-histamine diet response. Conversely, dermatographic urticaria and a hematocrit level<36% were significantly and inversely associated with low-histamine diet response. Conclusions. Several promising biomarkers were identified in this study to predict the efficacy of chronic urticaria treatment. DAO could be a novel biomarker for predicting the efficacy not only of dietary intervention but also for antagonists of H1 and H2 receptors.